Development of cash waqf framework investment- based ar-Rahnu model for Islamic pawn broking - Wan Ab Rahaman, Wan Mohd Al Faizee; Mat, Hamidah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Researchers have discussed the model and framework of cash waqf investment in Malaysia to give insight into the development of waqf in Malaysia's State Religion Islamic Councils (SIRCs). Whilst, ar-Rahnu is an Islamic pawn broking that objectively provides customers with financial well-being through pledging and borrowing. However, ar- Rahnu providers need more funds to provide borrowing funds, which increases from time to time and affects customers' interests. Therefore, ar-Rahnu providers should embark with new solutions to ensure institutions’ sustainability. As a result, this research aims to look into cash waqf investment models that can be implemented in ar- Rahnu's activities. This qualitative study used a data collection method in the form of content analysis. The data was analyzed based on inductive methods to obtain the result of the study. This paper found that cash waqf investment models have been extensively discussed, however, less of it has focused on the ar-Rahnu scenario. As a result of the paper's discussion, the ar-Rahnu framework based on the cash waqf investment model was developed. By utilising cash waqf in ar-Rahnu operations, ar-Rahnu can sustain and compete with other counterparties.